Oral bioavailability enhancement of agomelatine by loading into nanostructured lipid carriers: Peyer’s patch targeting approach - Prajapati JB (Dove Medical Press, 2018)
Jagruti B Prajapati, Sneha D Verma, Amit A Patel Department of Ppharmaceutics and Ppharmaceutical Technology, Rramanbhai Patel College of Ppharmacy, Charotar University of Science and Technology, Changa, Gujarat, India Abstract: Agomelatine (AGM) is a new antidepressant drug with a novel mechanism of action and fewer side effects compared with older antidepressants. AGM is a melatonin receptor (MT1 and MT2) agonist and 5-hydroxytryptamine receptor (5-HT2C) antagonist. In the present study, the enhancement of the oral bioavailability of AGM was formulated and loaded into nanostructured lipid carriers (NLCs), using ultrasonication method. In vitro and ex vivo drug release was performed using a dialysis bag and rat duodenum, respectively. Our pharmacodynamic study showed that AGM–NLCs are more efficacious than a pure drug and marketed product, and confocal microscopy revealed lymphatic uptake of AGM–NLCs. The present study concluded that the NLCs enhanced the oral bioavailability of AGM (6.5-fold) by avoiding its first-pass metabolism by way of lymphatic uptake. Keywords: agomelatine, nanostructured lipid carriers, antidepressant drug